KADAR KLOROFIL ALGA HIJAU Dictyosphaeria versluysii DAN UJI SENSORI PRODUK OLAHANNYA - Kurnia, Tri Santi; Ferdianti, Vicky; Pelamonia, Alamanda; Liline, Sintje (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background: Dictyosphaeria versluysii is a type of green algae that can be consumed. This alga is abundant in the coastal waters of Maluku Province. However, this alga has not been widely explored scientifically. Generally, people who live on the coast of Ambon Island and its surroundings do not know about the potential of Dictyospaheria versluysiii algae. This study aims to determine the chlorophyll content of green algae Dictyospaheria versluysiii and the level of public preference for processed products. Methods: Samples of green algae Dictyospaheria versluysii were taken by purposive sampling. Analysis of chlorophyll content using UV-Vis Spectrophotometry method at wavelengths of 645 nm and 663 nm. Sensory test using questionnaire with Likert scale on 35 panelists in Tulehu District, Central Maluku Regency. Results: Chlorophyll levels in three different samples, namely the untreated wet sample (Dv.2), the untreated dry sample (Dv.1), and the treated wet sample (Dv.3), have different results. The total chlorophyll levels for the three samples were 35.1 mg/L, 59.7 mg/L, and 18.6 mg/L, respectively. Sample Dv.1 had higher chlorophyll levels compared to the other two samples. The results of the sensory test showed that the parameters of color, taste, aroma, and level of liking were in the “Very Like” criteria and texture was in the “Like” criteria. Conclusion: The chlorophyll content of Dictyospaheria versluysiii algae decreased after processing. However, processed Dictyosphaeria versluysii algae products can be accepted by the people of Negeri Tulehu. This algae can be developed into useful alternative and innovative food.